Pengaruh Kinerja Keuangan Terhadap Cash Holding pada Perusahaan Sub Sektor Perbankan yang Terdaftar di Bursa Efek Indonesia Periode 2018-2020 - Fardianti, Rehanah; Astuti, Susi (Jurnal Ilmiah Manajemen Kesatuan, 2022)
This study aims to determine the effect of financial performance on cash holding. The population in this study is the banking sub-sector companies listed on the Indonesia Stock Exchange (IDX) in 2018-2020 as many as 45 companies. The research sample was 43 companies for 3 years so that a sample of 129 companies was obtained using purposive sampling method. Data analysis used the SPSS 25 program. The results showed that profitability (ROA) had a positive effect on cash holding, leverage (DER) had no effect on cash holding, and firm size had a negative effect on cash holding.